2019
DOI: 10.1016/j.celrep.2019.05.060
|View full text |Cite
|
Sign up to set email alerts
|

Injured Axons Instruct Schwann Cells to Build Constricting Actin Spheres to Accelerate Axonal Disintegration

Abstract: Highlights d Injured axons upregulate PlGF, which activates VEGFR1 in Schwann cells d VEGFR1 activates the formation of constricting actin spheres in Schwann cells d Constricting actin spheres accelerate the disintegration of injured axons d VEGFR1 expression in oligodendrocytes accelerates injured axon disintegration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 50 publications
(81 reference statements)
6
60
0
Order By: Relevance
“…Although they are unable to fully predict what happens at the whole organ level, primary SC/neuron cocultures have been useful PNS models to investigate the molecular mechanisms involved in axonal regrowth fostered by SCs and remyelination. Moreover, microfluidic devices, which allow the compartmentalization of neuronal cell bodies, axons and myelinating cells, have demonstrated to be useful in in vitro research [15,16].…”
Section: Nerve Injury and Methods In Regeneration Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Although they are unable to fully predict what happens at the whole organ level, primary SC/neuron cocultures have been useful PNS models to investigate the molecular mechanisms involved in axonal regrowth fostered by SCs and remyelination. Moreover, microfluidic devices, which allow the compartmentalization of neuronal cell bodies, axons and myelinating cells, have demonstrated to be useful in in vitro research [15,16].…”
Section: Nerve Injury and Methods In Regeneration Researchmentioning
confidence: 99%
“…The presence of persistent axon fragments inhibits the regeneration of axon branches [21] and leads to delayed axonal regrowth [16,41,42]. We recently showed that after a peripheral nerve lesion, SCs form constricting actomyosin spheres along unfragmented distal cut axons to accelerate their disintegration [16]. Interestingly, this mechanism is triggered by distal cut axons that upregulate the VEGFR1 agonist PlGF by injury-induced local translation, resulting in the activation of a VEGFR1/Pak1/F-actin axis in SCs [16].…”
Section: Axon and Myelin Clearancementioning
confidence: 99%
See 3 more Smart Citations